DESIGN AND EVALUATION OF FOUR STROKE CI ENGINEERING UTILIZING BIO DIESEL - et al., Rajeev Ranjan (International Journal of Advanced Science and Technology, 2020)
The focus of this research has been to Design & Evaluation of Four Stroke CI Engineering utilizingBio Diesel, since from last decade many research works are proposed on the performance of ICengine provided along ceramic coated combustion chamber, however they mainly focused ontheoretical advantages. Fewer efforts taken over the practical scenario of the engine provided alonginsulated combustion chamber. Due to the success have been reported from the engine along ceramiccoated combustion chamber, ceramic components are also developed which are utilizing like a part ofthe engine & are in service mainly for reduction of heat loss from combustion chamber walls. We alsonoticed that in many recent works the failures & drop in the performance of the engine providedalong ceramic coated combustion chamber. Thus the main research problem has been to design &evaluate the alternate solution for four strokes CI engineering utilizing the Bio-Diesel. In thisregards, we aim to utilize fuels directly in the engine along out any constructional modifications inthe engine results in damage in engine components. Also from bio-diesel because of its lower calorificvalue & higher viscosity, it has been difficult to extracts more benefits along these alternative fuels.Utilization of engine along ceramic coated combustion chamber has been effective solution toimprove performance of the engine & to decrease the exhaust emissions of these low-grade fuelswhen compared along normal diesel because it maintains higher temperature in the combustionchamber. We will present the design & experimental analysis of such systems in this research work.